Development of Science Board Game Based on Scaffolding Approach to Promote Collaborative Problem Solving Competency of Upper Secondary Students - Bubphaprom, Pantita; Chantraukrit, Pornthep (An Online Journal of Education, 2026)
The purpose of this research were to 1) develop a scaffolded science board game based on the to promote collaborative problem-solving competency among upper secondary school students, and 2) compare the collaborative problem-solving competency of upper secondary school students before and after using the board game. This study employed a research and development design consisting of three phases: 1) investigating the needs of and problems facing science teachers and students regarding the use of sufficiently scaffolded board games. Data were collected using a needs assessment questionnaire for biology teachers and upper secondary students and analyzed using frequency distribution, percentage, and content analysis for open-ended responses; 2) designing and developing a scaffolded science board game; and 3) implementing the developed board game with a purposively selected group of 30 students in grade 10. Data from this stage were collected through group-based observation using a collaborative problem-solving competency observation form. Descriptive statistics, including mean and standard deviation, and qualitative content analysis were used to analyze the data. The findings revealed that 1) the developed science board game with an Index of Item-Objective Congruence (IOC) ranging from 0.33 to 1.00 for board game design and 1.00 for content validity. Teachers and students expressed a strong need for instructional media that enhances collaboration and problem solving in an engaging and easy-to-understand format. Students reported a high to very high level of satisfaction with learning through the board game, and 2) the overall mean score of students’ collaborative problem-solving competency after using the board game was at a high level (M = 2.47).